Back Cover: ASBase: The universal database for aggregate science. Issue 1 (20th February 2023) - Gong, Junyi; Gong, Wanjun; Wu, Bo; Wang, Haoran; He, Wei; Dai, Zhongyang; Li, Yangzhong; Liu, Yong; Wang, Zhiming; Tuo, Xiaojun; Lam, Jacky W.Y.; Qiu, Zijie; et al.
Abstract : The ASBase, which is a universal database for aggregate science, is connecting the nodes in laborotary, industry and individuals with information and scientific data. (e263 )